2019
DOI: 10.4238/gmr18217
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Allelic and genotypic frequencies of the <i>DMRT3</i> gene in the Brazilian horse breed Mangalarga Marchador and their association with types of gait

Abstract: The DMRT3 gene has been described as the main gene influencing gait in horses; however, most studies have examined its effects by comparing information from trotted and gaited individuals. Within the Brazilian Mangalarga Marchador breed, animals can present two types of gaits (marcha batida and marcha picada), which differ in the movement form-diagonal (marcha batida) or lateral (marcha picada). We examined a possible association of the g.22999655C>A DMRT3 SNP with the type of gait, in this two-gaits breed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
2
11
0
2
Order By: Relevance
“…Recently, in the MM was suggested polygenic control over gait types, corroborating with the findings of Patterson, Staiger, and Brooks (2015) and Fonseca, Ferraz, Lage, Pereira, and Curi (2017) (see Bussiman et al., 2019). In addition, several candidate genes have been identified and associated with signatures of selection for both gait types (Santos, 2020).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Recently, in the MM was suggested polygenic control over gait types, corroborating with the findings of Patterson, Staiger, and Brooks (2015) and Fonseca, Ferraz, Lage, Pereira, and Curi (2017) (see Bussiman et al., 2019). In addition, several candidate genes have been identified and associated with signatures of selection for both gait types (Santos, 2020).…”
Section: Introductionsupporting
confidence: 71%
“…Studying pedigree representation in a genome‐wide association study in MM, Bussiman et al. (2019) reported that familiar structures are very common in horses, probably associated with a mating system based on the intense use of specific animals that achieve more awards in competitions.…”
Section: Discussionmentioning
confidence: 99%
“…The gaits are generally considered to be discrete patterns of footfalls and are divided into symmetrical and asymmetrical [ 27 ]. The allele A of the DMRT3 gene is only related to the picada gait in the MM, with two genotypes AA and CA, while the genotype CC is related to batida gait [ 28 ]; however, some studies have shown gait ability (the lateral gait pattern) is under the influence of a set of genes [ 5 , 29 ]. Other discoveries suggested that alleles related to the type of gait were differently fixed within each gait type [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been an established relationship between genotype at DMRT3 and the ability to pace (Han & Peñagaricano, 2016). For alternative gaits such as marcha batida, marcha picada in Brazilian Mangalarga Marchador horses (Bussiman et al., 2019, 2020; Fonseca et al., 2017; Patterson et al., 2015), rack and slow gait in American Saddlebred horses (Regatieri et al., 2016), Tölt in Icelandic horse (Fegraeus, Hirschberg, et al., 2017; Jaderkvist et al., 2015; Kristjansson et al., 2014), and Trocha and Colombian trot in Colombian horses (Novoa‐Bravo et al., 2018), the relationship with DMRT3 genotype was not so obvious and many other markers were found. We had attempted to predict the DMRT3 genotype using only the knowledge of trotting technique and failed, even if a strong difference in genotype frequency was found between main trotting technique characteristics.…”
Section: Discussionmentioning
confidence: 99%